Advancing hybrid ventilation in hot climates: a review of current research and limitations - Al Niyadi, Sheikha; Elnabawi Mahgoub, Mohamed H. (Frontiers in Built Environment, 2025)
IntroductionHybrid ventilation systems present a promising solution for reducing cooling energy consumption in buildings, particularly in hot climates. However, while existing research highlights their potential, variability in reported cooling energy reductions underscores the need for standardized performance evaluation methods.MethodsThis review synthesizes findings from 84 research articles published between 2010 and the first quarter of 2024. The studies include simulation-based analyses, experimental investigations, and real-world case studies sourced from prominent academic databases.ResultsThe review identifies substantial potential for cooling energy reductions through hybrid ventilation systems. However, it also reveals significant variability in energy savings across studies, suggesting that further work is needed to standardize reporting methods for accurate performance comparisons.DiscussionTo address these challenges, this paper proposes a framework integrating Industry 4.0 technologies. The framework emphasizes standardized research methodologies, context-specific design considerations, and robust knowledge dissemination strategies. Artificial Intelligence (AI) is positioned as a critical enabler of innovation, driving design optimization and smart control systems. The proposed framework aims to improve performance assessments, tailor system designs to specific building types and climates, and enable real-time control for enhanced energy efficiency and occupant comfort. This approach has the potential to support the wider adoption and optimized implementation of hybrid ventilation systems, contributing to a more sustainable and energy-efficient built environment, particularly in hot climates.